2020
DOI: 10.1108/bij-05-2020-0251
|View full text |Cite
|
Sign up to set email alerts
|

Exploring predictors of working capital management efficiency and their influence on firm performance: an integrated DEA-SEM approach

Abstract: PurposeThis study develops an integrated approach combining data envelopment analysis (DEA) and structural equation modeling (SEM) for estimating the working capital management (WCM) efficiency and evaluating the effects of diverse exogenous variables on the WCM efficiency and firms' performance.Design/methodology/approachDEA is applied for deriving WCM efficiency for 212 Indian manufacturing firms over a period from 2008 to 2019. Also, the effect of human capital (HC), structural capital (SC), cost of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 83 publications
5
42
0
1
Order By: Relevance
“…Moreover, both firm profitability and working capital are determined by multiple factors. From the perspective of potential endogeneity issue, the study of Seth et al (2020) is probably among the first that evaluates the impact of several exogenous variables on the WCM efficiency and firms' performance. Based on data envelopment analysis and structural equation modeling, the authors find that the following variables have a direct effect on WCM efficiency, and, therefore, on firms' performance: interest coverage, leverage, net fixed asset ratio, and asset turnover ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, both firm profitability and working capital are determined by multiple factors. From the perspective of potential endogeneity issue, the study of Seth et al (2020) is probably among the first that evaluates the impact of several exogenous variables on the WCM efficiency and firms' performance. Based on data envelopment analysis and structural equation modeling, the authors find that the following variables have a direct effect on WCM efficiency, and, therefore, on firms' performance: interest coverage, leverage, net fixed asset ratio, and asset turnover ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An increase in sales permits better management of commercial credit and inventories and helps firms avoid immobilisation of resources and price fluctuations (Mahmood et al, 2019). Seth et al (2021) and recognise that investments in working capital increase a company's negotiating power with its providers, allowing it to obtain larger discounts for bulk and down payments, thus increasing an organisation's value (Aktas et al, 2015;Deloof, 2003;Garc ıa-Teruel & Mart ınez-Solano, 2007). However, over-investment in working capital increases financing costs, reducing an organisation's value (Baños-Caballero et al, 2014;Chang, 2018;Zeidan & Shapir, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, over-investment in working capital increases financing costs, reducing an organisation's value (Baños-Caballero et al, 2014;Chang, 2018;Zeidan & Shapir, 2017). Research has made it possible to assume the existence of an optimal level of investment in working capital (Aktas et al, 2015;Baños-Caballero et al, 2012;Khan & Ghazi, 2013), as studies have identified a non-linear relationship between investment in working capital and financial performance (Ding et al, 2013;Seth et al, 2021). This non-linear relationship suggests the existence of an optimum investment in working capital (Mahmood et al, 2019) Numerous studies have been conducted in developed economies to estimate the true relationship between investment in working capital and financial performance, but it is possible that these results cannot be extrapolated to emerging economies due to their different social, political, and economic contexts (Seth et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2017) used DEA models to measure the comparative performance of 18 Korean commercial banks in the presence of negative observations and examined the difference in performance among these banks. Seth et al (2021) used DEA models to explore the predictors of working capital management performance and their influence on firm performance. The results of this study evaluated the impact of various exogenous variables on the efficiency of working capital management and the performance of companies.…”
Section: Introductionmentioning
confidence: 99%